Application of the reaction of O-phenylenediamine with various carbonyl compunds in the synthesis of different heterocyclic compounds of expected therapeutic acctivity - Eman Omar Mahmoud Osman; Maha Abdelhakeem; Mohamed Abdelrahman Shaaban; Omneya Mahmoud Khalil (Cairo : Eman Omar Mahmoud Osman, 2014)
This thesis comprises four chapters in addition to references and arabic summary. the first one involved the introduction which included the reactions of o-phenylenediamine and carbonyl compounds. the second chapter clarified the aim of the work and the schemes adopted for the preparation of the target compounds
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Organic Chemistry
Issued also as CD
Keywords: Analgesic activity; Carbonyl compounds; O-phenylenediamine